Identification of nitrosamine precursors from urban drainage during storm events: A case study in southern China. (October 2016) - Bei, Er; Liao, Xiaobin; Meng, Xiangting; Li, Shixiang; Wang, Jun; Sheng, Deyang; Chao, Meng; Chen, Zhuohua; Zhang, Xiaojian; Chen, Chao
Abstract: The drinking water sources of many cities in southern China are frequently contaminated by upstream urban drainage during storm events, which brings high concentrations of N -nitrosamine (NA) precursors and poses a threat to the safety of drinking water. We conducted two sampling campaigns during the heavy rain season in 2015 in one representative city in southern China. We detected that the concentration of N -nitrosodimethylamine formation potential (NDMA FP) in urban drainage during two storm events was 80–115 ng/L and the total formation potential concentration of nine nitrosamines (TNA9 FP) was 145–165 ng/L. To address the deteriorated water quality, 30 mg/L of powdered activated carbon (PAC) was fed into the water intake. PAC adsorption alone could remove 52% of NDMA FP and 52% of TNA FP, while the subsequent conventional process only removed 8% of TNA FP. We isolated six chemicals ( N, N -benzyldimethylamine, 5-[(dimethylamino)methyl]-2-furanmethanol, N, N -dimethyl-3-aminophenol, N, N -dimethylethylamine, Ziram, and N, N -dimethylaniline) and confirmed them to be NA precursors. Among these NA precursors, Ziram was identified for the first time as a NA precursor that is formed via chloramination; its molar yield for NDMA was 6.73 ± 0.40%. Graphical abstract: Highlights: Nitrosamine (NA) precursors from drainage during storm event was firstly investigated. Formation potential (FP) of total NAs in storm drainage were about 100 ng/L. Powdered activated carbon removed 52% of NA FP while conventional process removed 10%. Ziram was screened as a new NA precursor via chloramination among six NA precursors.